2017
DOI: 10.3126/jnhrc.v15i1.18006
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Waste Management Practice in Health Care Institutions of Nepal

Abstract: INTRODUCTION

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 7 publications
1
29
0
3
Order By: Relevance
“…Moreover, around 83% of the selected health care facilities in Ghana did not segregate their medical waste. A study done by Joshi (2013) indicated that in Nepal, around 1.7 kg bed −1 day −1 waste was produced. Of which, 0.48 kg bed −1 day −1 generated waste was found to pose health risks (Table 3).…”
Section: Hospital Waste Management Systems In Different Developing Comentioning
confidence: 99%
“…Moreover, around 83% of the selected health care facilities in Ghana did not segregate their medical waste. A study done by Joshi (2013) indicated that in Nepal, around 1.7 kg bed −1 day −1 waste was produced. Of which, 0.48 kg bed −1 day −1 generated waste was found to pose health risks (Table 3).…”
Section: Hospital Waste Management Systems In Different Developing Comentioning
confidence: 99%
“…Nepal has an IPC reference manual that serves more as a resource for training purposes than for the actual development of IPC programmes. 11 There are some IPC-specific materials available for both HIV and waste management in the country 12 ; however, comprehensive national guidelines on IPC, reflecting performance indicators, do not currently exist. As a result, over two-thirds of the healthcare workers in Nepal are deficient in specific training in IPC.…”
Section: Nepalmentioning
confidence: 99%
“…Health care waste management would be challenge for developing countries. There is relation between health care facilities and health waste generation [5]. Medical waste generated in department of surgery is highest on daily bases (3-4 times).…”
Section: Introductionmentioning
confidence: 99%